Optimising physiological recovery after high-intensity training: A combined approach of hydrotherapy, contrast bath, and full-body massage in futsal players - Nugraha, Afif Dwi; Andriana, Laily Mita; Antoni, Muhamad Fauzi; Rasyid, Muhammad Labib Siena Ar; Lestari, Bhekti (CV Rezki Media, 2025)
Background: Efficient recovery after high-intensity interval training (HIIT) is crucial for maintaining optimal performance and minimizing the risk of injury. Objectives: This study aims to analyze the effectiveness of combining hydrotherapy contrast baths and full-body massage in accelerating physiological recovery after a HIIT session, compared to the application of a single method. Methods: This study employed a pre–post quasi-experimental design with three parallel groups (n = 45; 15 participants per group) to analyze the effectiveness of hydrotherapy combined with whole-body massage compared with each method applied separately. Participants were assigned to one of three conditions: (1) hydrotherapy contrast bath only, (2) full-body massage only, and (3) a combined intervention using both techniques. Physiological recovery was assessed using validated instruments, including heart rate monitors for heart rate recovery (HRR), portable lactate analysers for blood lactate concentration, and a visual analogue scale (VAS) for perceived muscle soreness. Data were analysed using the Shapiro–Wilk test, paired-sample t-test, and One-Way ANOVA. Results: The findings demonstrated that the combined hydrotherapy–massage protocol resulted in greater improvements than the single-method groups, particularly in lactate reduction (e.g., -3.1 ± 0.8 mmol/L vs. - 1.9 ± 0.7 mmol/L and - 2.0 ± 0.6 mmol/L; p<0.05) and faster HRR. Participants in the combined group also reported significantly lower muscle soreness (p<0.05). Conclusions: This suggests that integrating contrast bath hydrotherapy with full-body massage enhances circulation, accelerates metabolic waste clearance, and improves subjective recovery following HIIT. Future studies are recommended to include larger samples, compare different hydrotherapy temperatures, or examine long-term adaptations from repeated recovery sessions.